An unusual cause of edema in a child with congenital heart disease post Fontan procedure - Wade, Minal; Shettiwar, Shweta; Shah, Ankita (International Journal of Research in Medical Sciences, 2019)
Protein Losing Enteropathy Post Fontan procedure. Protein Losing Enteropathy (PLE) is an uncommon cause of edema in children with congenital heart disease. Protein-Losing Enteropathy may be defined as excessive loss of proteins across the intestinal mucosa and is due to either a primary gastrointestinal abnormality or secondary to cardiac disease. Protein-losing enteropathy (PLE) is a rare complication of the Fontan palliation for functional single-ventricle. Although PLE occurs in about 3.5% of patients post-Fontan, it confers marked morbidity and high mortality within 5 years of diagnosis. The pathogenesis of Fontan-related PLE is not completely understood, and it is unclear why it develops in some patients post-Fontan and not others. We describe a child with Double Inlet Right Ventricle who had undergone Fontan procedure, and presented to us with generalised oedema. The child had hypoproteinaemia, the common causes for which were ruled out and was diagnosed as Protein Losing Enteropathy (PLE) related to his surgical intervention. Though, not frequently encountered it should be kept in mind as one of the causes of anasarca.